Neutrophil activation signature in juvenile idiopathic arthritis indicates the presence of low-density granulocytes. (12th December 2017) - Ramanathan, Kavitha; Glaser, Anna; Lythgoe, Hanna; Ong, Joanne; Beresford, Michael W; Midgley, Angela; Wright, Helen L
Abstract: Objective: JIA is an autoimmune, inflammatory disease with involvement of innate and adaptive immune responses. However, the role of neutrophils in JIA pathogenesis remains unclear. This study aimed to identify and validate neutrophil gene expression signatures in JIA using public microarray datasets and new clinical samples. Methods: Three suitable datasets were analysed by significance analysis of microarray and Ingenuity. Neutrophils and peripheral blood mononuclear cells (PBMCs) were isolated from a new cohort of JIA patients and healthy paediatric controls (HCs). Gene expression was validated using quantitative PCR. Serum concentrations of proteins were measured using ELISA. Low-density granulocytes (LDGs) in JIA and HC PBMCs were quantified by flow cytometry using forward/side-scatter properties. Results: Ingenuity identified transcriptional regulation (false discovery rate < 0.05) by G-CSF, GM-CSF and IL-8 along with expression of neutrophil granule protein genes including ELANE, MPO, MMP8 and MMP9 in datasets from JIA PBMCs. LDG counts were elevated in JIA compared with HCs (2.5% vs 1.4%; P = 0.007). Transcripts for MMP8 ( P = 0.005), MPO ( P = 0.0124) and Fcγ Receptor 1B ( FCγR1B ) ( P = 0.0417) were significantly higher in JIA compared with HC neutrophils. MMP9 protein levels were lower in systemic JIA patient sera [355.95 ng/ml (s .d . 250.03)] compared with HCs [675.41 ng/ml (s .d . 181.17); P = 0.007], but levels of elastase, MPO and MMP8 were not significantly different. Conclusion: LDGs are elevated in JIA and contribute to the transcriptomic profile of JIA PBMCs. JIA neutrophils express higher levels of MMP8 and FCGR1B, which may be implicated in disease pathology through the release of proteases and reactive oxygen metabolites, causing systemic inflammation and damage to joints.